Experts reports in engineering and construction arbitrations. Difficulties that arbitrators and experts must deal with. Some proposals from practical experience - Ríos Salas, Víctor (2020)
During the development of an expert report, difficulties arise that may have a significant impact on its probatory value. This can be noted in the selection of the expert; in determining the scope of the report; in the form of access to the documentation of the process; in communications that the expert may or may not have with the parties, their respective experts, and with the arbitrator; in the selection of methodologies to evaluate costs and extensions of time; in legal matters related to the technical aspects of the report; in the expert hearing; and in the content of the report itself. In this article we will seek to identify the difficulties that usually arise, with some proposals of possible solutions.